Mozaik Arkeologi di Ujung Negeri, Potensi dan Prospeknya - Nenggih Susilowati (Balai Arkeologi Sumatera Utara, 2011)
AbstractThe cultural history trace of Natuna is the description of a series of activities which take place in the region since prehistoric to historic time. Another one also describe about migration flows. Some cultural description can be got from some archaeological object which can be developed for some importance.